(untitled) (International Journal of Engineering and Computer Science, 2016)
Destination prediction technique involves tracking the trace of the moving objects with the positioning services like GPS equipped devices. Destination prediction is also called path discovery to find most suitable path that satisfy predefined objective between source and destination. Trajectory is represented by a sequence of time stamped geographical location. Trajectories provide intelligence to estimate, compare and construct candidate routes by historical road network. All trajectories are decomposed into sub-trajectories and then synthesized-trajectories are generated by connecting sub-trajectories together. Moving objects can be human being, animals, vehicles and even natural phenomenon (e.g., Hurricanes). Mobility pattern of the user is predicted using next check-in data. Prediction features that exploit different information dimensions about users based on venue prediction.